Volume 11: Nano and Micro Materials, Devices and Systems; Microsystems Integration 2011
DOI: 10.1115/imece2011-64168
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties of Carbon-Infiltrated Carbon Nanotube-Templated Structures for Microfabrication of Compliant Mechanisms

Abstract: Carbon nanotubes can be grown vertically from a substrate to form dense forests hundreds of microns tall. The space between the nanotubes can then be filled with carbon using chemical vapor deposition to create solid structures. These infiltrated structures can be detached from the substrate and operated as single-piece MEMS. To facilitate the design of compliant microdevices using this process, we explored the influence of two fabrication parameters—iron layer thickness and infiltration time—on the material’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…A statistical analysis of this data shows that the infiltration time has a significant effect on both the ultimate strength and the elastic modulus, but not on maximum strain. There is also an interaction of infiltration time with iron thickness that significantly affects the elastic modulus, although iron thickness on its own was not found to directly affect the three properties studied here [14].…”
Section: A Cantilever Testsmentioning
confidence: 88%
See 3 more Smart Citations
“…A statistical analysis of this data shows that the infiltration time has a significant effect on both the ultimate strength and the elastic modulus, but not on maximum strain. There is also an interaction of infiltration time with iron thickness that significantly affects the elastic modulus, although iron thickness on its own was not found to directly affect the three properties studied here [14].…”
Section: A Cantilever Testsmentioning
confidence: 88%
“…Comparing the finite element results to the test results, we used an iterative process to calculate corrected values of the Young's modulus and failure stress for each sample. This finite element model and correction procedure is described in greater detail in [14].…”
Section: Nonlinear Fea Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Ref. [18], initial experiments with carbon deposition have shown that carbon-infiltrated structures exhibit a remarkable degree of compliance and strain in bending, where tension is the typical failure mode. The high strain and superior biocompatibility marks CI-CNT as a potentially appropriate and even superior material to typical steels and alloys for stent fabrication.…”
Section: Introductionmentioning
confidence: 97%